Mini-laparotomy with Adjunctive Care versus Laparoscopy for Placement of Gastric Electrical Stimulation. Issue 4 (April 2016) - Smith, Alison; Cacchione, Robert; Miller, ED; Mcelmurray, Lindsay; Allen, Robert; Stocker, Abigail; Abell, Thomas L.; Hughes, Michael G.
We compared outcomes for two gastric electrical stimulation placement strategies, mini-laparotomy with adjunctive care (MLAC) versus laparoscopy without adjunctive care (LAPA). For electrode placement, the peritoneal cavity was accessed with either a single 2.5 to 3.0 cm midline incision (MLAC) or three trocar incisions (LAPA). For both groups, generator was placed subcutaneously over the anterior rectus sheath. For MLAC, adjunctive pain control measures were used for placement of both electrode and generator (transversus abdominus plane block). For LAPA, those that could not be completed by laparoscopy were converted to traditional open approach and kept in the analysis. MLAC (n = 128) resulted in shorter operative times than LAPA (n = 37) (median operative time: 87.5 vs 137.0 minutes, P ≤ 0.01). Hospital length of stay was also shorter for MLAC than for LAPA (median: 2.0 vs 3.0 days, P ≤ 0.01) without any increase in readmission rates to the hospital within 30 days of discharge (11.0 vs 16.2%, P = 0.39). After equalizing learning curves, these differences were even greater (median operative time: 84.5 vs 137.0 minutes, P < 0.01; median length of stay: 1.0 vs 3.0 days; P < 0.01) without increasing 30-day read-mission rates (9.1 vs 16.2%, P = 0.25). For implantation of gastric electrical stimulators, mini-laparotomy can result in improved outcomes when coupled with adjunctive pain control measures.